Ekspresi Diri, Identitas Kolektif, dan Resolusi Konflik: Peran Bahasa Cia-Cia dalam Dinamika Sosial Komunitas Dusun Rahai - Tomia, Asrul; Lopulalan, Dortje Leonora Yokbeth; Nahuway, Johana (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study explores the role of the Cia-Cia language in shaping the social dynamics of the Dusun Rahai community, particularly in fostering self-expression, collective identity, and conflict resolution. Utilizing a qualitative method through participatory observation and in-depth interviews with both younger and older generations, the research finds that Cia-Cia serves not only as a means of daily communication but also as an educational tool that imparts social values from an early age. Regular use of the language develops key social skills, including building interpersonal relationships, understanding others’ emotions and needs, resolving conflicts peacefully, and managing social emotions. Beyond its communicative function, Cia-Cia strengthens speakers’ confidence and comfort in expressing personal thoughts and feelings, reinforcing the community’s shared identity. The language also acts as an intimate and symbolic medium, often perceived as a “secret language” within social interactions. The novelty of this study lies in revealing Cia-Cia’s dual function as both a social and cultural mechanism that sustains community cohesion and manages conflicts harmoniously. This research emphasizes the critical need to preserve indigenous languages like Cia-Cia as strategic assets in advancing social and political sciences, especially in studies of language, culture, and community resilience.